Slit skin smear or Fite-Faraco staining of tissue sample, which is a better indicator of bacillary load? - Appannavar, Shruti; ., Kiran; Ingalagi, Amit Ashok; ., Rohith (International Journal of Research in Dermatology, 2021)
Background: Leprosy is clinically diagnosed on the basis of presence of following cardinal signs: 1. Hypopigmented or erythematous anesthetic patch on skin, 2. Thickened and/or tender peripheral/cutaneous nerve, 3. Acid fast bacilli in slit skin smear. This study aims at comparing bacillary indices in slit skin smears with that from biopsy samples. Methods: After obtaining informed written consent, slit skin smears were performed and observed for acid fast bacilli. Punch biopsies of lesions were taken and processed and stained with Fite-Faraco technique. The presence or absence of acid-fast bacilli in both modalities was noted. Results: Slit skin smears were positive in 24 patients and negative in the rest. And 26 patient’s biopsy reports had Fite-Faraco positivity, out of the total 46 patients. The p=0.67 which was not significant at significance value 0.05. Conclusions: Skin smear is an equally reliable indicator of bacillary load as Fite-Faraco bacillary index in tissue.